الآراء النحوية في المرفوعات عند ابن جني في كتاب همع الهوامع للسيوطي جمعا ودراسة - حسن, المشرفة: أ.م.د. إسراء ياسين; كريم, والي رحيم عبدالرحمن (Sulaimani Journal for Humanities, 2023)
This study deals with the nlost significant gramma Tical lssues of, Nouns with regular ending, in the book of, Hama al Hawama Alsiuti, and extracting Ibn jinni is opinion in his books in cluding, Hama Al-Hawama Alsiuti, and in Other scholar is books. All view poits of Ibn Jinni in, Nouns with regular ending, involve eight subjects .preceded by an In troduction and Nouns with regular ending, she Dual, and Primate and predicate and Kaena and its sisters and Primate Repetition and predicate plurality return on the informant (Primate) From the sum of the two news, and Presentation of the implied on the appearance of the pronunciation and meaning and the pro-agent and the noun in the genitive case and the preposition. And then I put a conclusion that included the most important results that I reached
Keywords: المرفوعات والمثنى والمبتدأ والخبر وتكرار المبتدأ وكان وأخواتها وتقديم المضمر على مظهر لفظا ومعنى والظرف والمجرور وما يتعلقان به إذا وقعا خبرا ونيابة (الفاعل) الجاروالمجرور